A missão da Igreja na contemporaneidade à luz do Vaticano II: Os desdobramentos da teologia da missão nas Conferências Gerais do Episcopado Latino-Americano e Caribenho - Módena, Hernane Santos (2021)
This research aims to address in a critical and analytical way the theme of Missiology that emerged in the Second Vatican Council and its post-conciliar walk, as well as its development in the General Conferences of the Latin American and Caribbean Episcopate, from Medellín to Aparecida. Against the background of the historical context, in its political, economic, social and ecclesial aspects, an overview of the Second Vatican Ecumenical Council will be presented, with emphasis on the ecclesiological and pastoral dimensions, by referring to the documents that address the missionary activity of the Church, especially the Decree Ad Gentes, as a watershed for the theology of mission. It will also analyze some features of the main events and pontifical documents in the post-Vatican II that had as their theme the missionary nature of the Church, seeking to understand the development of the theology of mission, its relations and ecclesial impacts in the world. Placing the "missiological magnifying glass" in this period, from the celebration of Vatican II to the General Conferences of the Bishops of Latin America and the Caribbean, is of highly importance to deepen the knowledge of the identity and mission of the Church present in this continent; as well as contributing to better evangelizing and pastoral action in the face of the old and new challenges present in today‟s context